2022
DOI: 10.1038/s41598-022-07642-1
|View full text |Cite
|
Sign up to set email alerts
|

UCHL5 controls β-catenin destruction complex function through Axin1 regulation

Abstract: Wnt/β-catenin signaling is crucially involved in many biological processes, from embryogenesis to cancer development. Hence, the complete understanding of its molecular mechanism has been the biggest challenge in the Wnt research field. Here, we identified ubiquitin C-terminal hydrolase like 5 (UCHL5), a deubiquitinating enzyme, as a novel negative regulator of Wnt signaling, upstream of β-catenin. The study further revealed that UCHL5 plays an important role in the β-catenin destruction complex, as it physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Full length of mouse Axin1 and human AXIN1 constructs were kindly provided by Dr. Frank Costantini. The -catenin CTNNB1 constructs were obtained as described previously 50 . Point and deletion mutagenesis were used to generate catalytic-dead (D82A, H115Q) and deletion ( DYFL) mutants of ppp4c , and the truncated forms (1–433, 434–826, 65–826, 65–545, and 396–826) of mouse Axin1 .…”
Section: Methodsmentioning
confidence: 99%
“…Full length of mouse Axin1 and human AXIN1 constructs were kindly provided by Dr. Frank Costantini. The -catenin CTNNB1 constructs were obtained as described previously 50 . Point and deletion mutagenesis were used to generate catalytic-dead (D82A, H115Q) and deletion ( DYFL) mutants of ppp4c , and the truncated forms (1–433, 434–826, 65–826, 65–545, and 396–826) of mouse Axin1 .…”
Section: Methodsmentioning
confidence: 99%
“…We generated stable HeLa cell lines which expressed b-catenin* and the aromatic mutants from a DOX-inducible expression cassette via lentiviral transduction. We chose to assay the Wnt target genes Axin2 and Sp5 as they are strongly activated by Wnt signaling in HeLa cells [36,37]. qPCR analysis of HeLa cells expressing b-catenin* and the aromatic mutants indicates that the relationship between aromatic amino acid residues and gene regulation is slightly more complex than the reporter activity (Fig 4A).…”
Section: Aromatic Amino Acid Residues Within B-catenin's Idrs Are Cri...mentioning
confidence: 99%
“…These stabilizing influences have been documented through various mechanisms. Reports have indicated that deubiquitinating enzymes, including USP7 [ 69 ], USP44 [ 70 ], USP49 [ 71 ], and UCHL5 [ 72 ], can reduce the ubiquitination of AXIN1, thereby hampering WNT/β-catenin signaling. DAB2 contributes to an increase in the protein level of AXIN1 by impeding the dephosphorylation of PP1 on AXIN1 [ 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%